Systematic Analysis of Molecular Characterization and Clinical Relevance of Liquid–Liquid Phase Separation Regulators in Digestive System Neoplasms - Zhang, Yaxin; Li, Jie; Feng, Dan; Peng, Xiaobo; Wang, Bin; Han, Ting; Zhang, Yingyi (Frontiers in Cell and Developmental Biology, 2022)
Abstract Background: The role of Liquid-Liquid Phase Separation (LLPS) in cancer has also attracted more and more attention, which was found to affect transcriptional regulation, maintaining genomic stability and signal transduction, and contribute to the occurrence and progression of tumors. However, the role of LLPS in digestive system tumors is still largely unknown. Results: Here we characterized the expression profiles of LLPS regulators in 3 digestive tract tumors types like COAD, STAD, ESCA with The Cancer Genome Atlas (TCGA) data. Our results for the first time showed LLPS regulatory factors, such as Brd4, FBN1 and TP53, were frequently mutated in all types of digestive system tumors. Variant Allele Frequency (VAF) and APOBEC analysis demonstrated Genetic alterations of LLPS regulators were related to the progression of Digestive System Neoplasms, such as TP53, NPHS1, TNRC6B, ITSN1, TNPO1, PML, AR, BRD4, DLG4 and PTPN1. KM plotter analysis showed mutation status of LLPS regulators were significantly related to the OS of DSNs, indicating that they may contribute to the progression of DSN. The expression analysis of LLPS regulatory factors showed that a variety of LLPS regulatory factors were significantly dysregulated in digestive system tumors, such as SYN2 and MAPT. It is worth noting that we first found that LLPS regulatory factors were significantly correlated with tumor immune infiltration of B cells, CD4 + T cells and CD8 + T cells in digestive system tumors. Bioinformatics analysis showed The LLPS regulators expression was closely related to multiple signaling, including ErbB signaling pathway, T cell receptor signaling pathway. Finally, several LLPS signatures was constructed and had a strong prognostic stratification ability in different digestive gland tumors. Finally, the results demonstrated the LLPS regulators signature score was significantly positively related to the infiltration levels of CD4+ T cells, Neutrophil cells, Macrophage cells, and CD8+ T cells. Conclusions: Our study for the first time showed the potential roles of LLPS regulators in carcinogenesis and provide novel insights to identify novel biomarkers for the prediction of immune therapy and prognosis of Digestive System Neoplasms.